Effect of drought stress on natural rubber biosynthesis and quality in Taraxacum kok-saghyz roots. - Seyed Shahab Hedayat Mofidi; Mohammad Reza Naghavi; Manijeh Sabokdast; Parisa Jariani; Meisam Zargar; Katrina Cornish (PLoS ONE)
Taraxacum kok-saghyz (TKS) is a potential source of natural rubber (NR) that can be grown in temperate regions with limited water availability. However, the effect of drought stress on NR production and properties in TKS isn't well studied. This study examined how different levels of drought stress (30, 60 and 90%) influenced the NR content, molecular weight (Mw), glass transition temperature (Tg), gene expression, and biochemical parameters in TKS roots. The results showed that drought stress didn't significantly change the NR content, but increased the Mw and the expression of CPT and SRPP genes, which are involved in NR biosynthesis. The NR from TKS roots (TNR) had a high Mw of 994,000 g/mol and a low Tg of below -60°C under normal irrigation, indicating its suitability for industrial applications. Drought stress also triggered the accumulation of proline, H2O2, MDA, and antioxidant enzymes (CAT, APX, GPX) in TKS roots significantly, indicating a drought tolerance mechanism. These findings suggest that TKS can produce high-quality NR under drought stress conditions and provide a sustainable alternative to conventional NR sources.